2017
DOI: 10.20473/j.djmkg.v50.i2.p55-60
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of sarang semut extract (Myrmecodia pendens Merr & Perry) in inhibiting Porphyromonas gingivalis biofilm formation

Abstract: Background: Porphyromonas gingivalis (P. gingivalis) is a pathogenic bacteria present in the oral cavity involved in the pathogenesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…Ant nest plants display antibacterial properties. Alibasyah et al [40] found that compounds derived from M. pendans ethyl acetate extract, specifically diterpenoids and biflavonoids, exhibit antibacterial properties against P. gingivalis, as determined by the Kirby-Bauer method. In the study, six iridoids showed antibacterial activity against S. aureus, each with a minimum inhibitory concentration (MIC) above 100 μg/mL, while the MICs for the other two were 19.57 and 39.06 μg/mL.…”
Section: Potential Of Myrmecodia Spp As An Antibacterial Agentmentioning
confidence: 99%
“…Ant nest plants display antibacterial properties. Alibasyah et al [40] found that compounds derived from M. pendans ethyl acetate extract, specifically diterpenoids and biflavonoids, exhibit antibacterial properties against P. gingivalis, as determined by the Kirby-Bauer method. In the study, six iridoids showed antibacterial activity against S. aureus, each with a minimum inhibitory concentration (MIC) above 100 μg/mL, while the MICs for the other two were 19.57 and 39.06 μg/mL.…”
Section: Potential Of Myrmecodia Spp As An Antibacterial Agentmentioning
confidence: 99%
“…Several species of them have been successfully identified, M. pendens contained kaempferol, luteolin, rutin, quercetin and apigenin, rosmarinic acid, procyanidin B1, the polymer of procyanidin B1, gallic acid, (+)-catechin, caffeic acid, p-coumaric acid, and ferulic acid [7], [31], [32]. Some researchers reported that phenolic glycoside with aliphatic moiety [13], dibenzo-p-dioxin-2,8-dicarboxylic acid [33], guaiacol, 1,4-di-tert-butoxybenzene, 4-methylcatechol and 2,6-dimethoxy-phenol [34], anthocyanin [35] and biflavonoid [36] have been isolated from M. pendens. Other isolates of flavonoid and phenolic compounds were found in M. platytyrea such as, acylated flavanone, flavanone (liquiritigenin or isoliquiritigenin), O-methylated isoflavone (calycosin) and 2-(2-methylbutyryl) phloroglucinol glucoside [37].…”
Section: Phytochemistrymentioning
confidence: 99%
“…and Bacillus sp. [15], Candida albicans, Staphylococcus aureus [38], Streptococcus mutans [39], Shigella dysenteriae [40], Streptococcus sanguinis [41], [42], [43], Enterococcus faecalis [34], [44], Porphyromonas gingivalis [45] and Treponema denticola [42]. activity against P. gingivalis pathogen using Kirby-Bauer method with minimum inhibitory concentration (MIC) of 19.57 µg/mL and 39.06 µg/mL, respectively [36].…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical trauma to the pulp treatment procedure cannot be avoided especially if caries expand to deep depths. The action of cavity preparation or removal of carious tissue in deep cavities can cause pulp perforation 1 . Pulp perforation can be caused by the use of burs or other dental tools.…”
Section: Introductionmentioning
confidence: 99%